MENINGKATKAN KECERDASAN INTERPERSONAL MELALUI METODE PROYEK ANAK USIA 5 – 6 TAHUN DI TK PELITA HATI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - ', Mahlinda; ', Wilson; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve interpersonal intelligence through the project method in children aged 5-6 years in kindergarten Pelita Hati Lubuk Terentang District of Gunung Toar Regency Kuantan Singingi. Project method chosen because it can encourage children to increase social sensitivity, social understanding and social communication. This research is a classroom action research subjects in this study is children aged 5-6 years in kindergarten Pelita Hati Lubuk Terentang District of Gunung Toar Regency Kuantan Singingi number of children 16. The object of this research is interpersonal intelligence of children, which includes three-dimensional social sensitivity, social understanding and social communication. Data collection methods used were observation and documentation. Data were analyzed using descriptive statistical analysis to find the average value and the percentage of successful children. The research hypothesis is interpersonal intelligence can be improved through the project method in children aged 5-6 years in kindergarten Pelita Hati Lubuk stretched Regency Kuantan District of Mount Toar Singingi. It can be seen from the analysis of data obtained cycle I gained an average of 46.52%,. and the second cycle was obtained by an average of 77.68%, this research indicates that interpersonal intelligence of children increased after their action through project methods.